2014
DOI: 10.1097/dcr.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transversus Abdominis Plane Blocks on Postoperative Pain in Laparoscopic Colorectal Surgery

Abstract: Transversus abdominis plane blocks improved immediate short-term opioid use and pain outcomes. Pain improvement was durable throughout the hospital stay. However, the blocks did not translate into less overall narcotic use, shorter length of stay, or lower readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 37 publications
1
74
0
1
Order By: Relevance
“…Another method of visualized infiltration is administration during laparoscopic procedures [15,16]. This nerve blockade, typically utilized for TAP blocks, is performed during pneu- moperitoneum with direct laparoscopic visualization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method of visualized infiltration is administration during laparoscopic procedures [15,16]. This nerve blockade, typically utilized for TAP blocks, is performed during pneu- moperitoneum with direct laparoscopic visualization.…”
Section: Discussionmentioning
confidence: 99%
“…This method similarly attempts to eliminate potential complications, specifically colonic or small bowel perforation which has been described with the other administration techniques. Proponents also note that there is little to no learning curve with this method which takes advantage of tactile sensation and laparoscopic visualization [15,16]. Though the incidence of FNP following II/IH-NB is an uncommon occurrence, it does represent a potential risk to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the change in patient pain scores was deemed significant, opioid use did not meet the threshold for statistical significance, which the authors attributed to early motility and lower narcotic intake at POD 0 in the treatment group. 23 This inconsistency was again shown in a similar trial by Fields and colleagues, 24 which followed 52 patients and evaluated the effect of transversus abdominis plane block on postoperative pain and opioid consumption immediately following ventral hernia repair surgery and up to POD 1. Although this trial reported a significant decrease in cumulative opioid use and postoperative pain experienced by patients in the treatment group, the difference in pain scores reached statistical significance much earlier than narcotic use (1 hr postoperative v. 6 hr postoperative).…”
Section: Is There Strong Evidence That a Change In The Surrogate End mentioning
confidence: 97%
“…24 Although these RCTs show a consistent association between narcotic use and postoperative pain, the strength of this correlation is not clear. Specifically, Keller and colleagues 23 and Fields and colleagues 24 reported that postoperative pain scores appeared to reach statistical significance, whereas narcotic use did not. Although the reason for this is not certain, the literature continues to report the role of additional variables that may affect opioid consumption.…”
Section: Is There Strong Evidence That a Change In The Surrogate End mentioning
confidence: 99%
See 1 more Smart Citation